CONVERGENCE OF ACCOUNTING STANDARDS, FINANCIAL TRANSGRESSION AND REGULATORY REFORMS IN INDIA AND USA - et al., Mr. Manav Aggarwal (International Journal of Advanced Science and Technology, 2019)
The purpose of the study is to find the various reasons of financial transgression in India and USA and evaluation of subsequent changes made thereafter by regulatory bodies in the statutes so that no such cases occur in future. Secondary sources of information are used to cover cases of financial transgression in India and USA for the period 1991 till 2018. Major loopholes have been found in Indian regulatory framework rather than in USA. It is observed that even after USA proactively changed the rules, yet the financial transgression cases could not be fully eliminated by them. The timeline of the cases in India and USA is strategically hinting towards the weak regulatory system of India along with late changes made in the relevant regulatory framework. Remarkable reduction in number of cases of financial transgression has been reported but India has not learnt a lesson from US corporate failures.